Management of Class II malocclusion with ectopic maxillary canines - Rohan Mascarenhas; Shahista Parveen; Tariq Aziz Ansari (Wolters Kluwer Medknow Publications, 2015)
Correction of Class II relationship, deep bite and ectopically erupting canines is an orthodontic challenge for the clinician. A 13-year-old male patient presented with Class II malocclusion, ectopically erupting canines, and cross bite with maxillary left lateral incisor. He was treated with a combination of Headgear, Forsus TM fatigue resistant device [FFRD] with fixed mechanotherapy for the management of space deficiency and correction of Class II malocclusions. Headgear was used to distalize upper first molars and also to prevent further downward and forward growth of the maxilla. Then Forsus TM FFRD was used for the advancement of the mandible. The molar and canine relationship were corrected from a Class II to a Class I. The objectives were to establish good occlusion and enable eruption of unerupted canines. All these objectives were achieved and remained stable.